STUDY OF POLYSACCHARIDES IN THE MEDICINAL PLANT RAW MATERIALS OF CREEPING THYME - Зарівна, Надія (SWorldJournal, 2022)
The paper presents the study of polysaccharides in medicinal plant raw materials of creeping thyme.The medicinal plant raw materials under study contains a complex complex of biologically active substances (BAS) with diverse pharmacological effects: flav